Study on the acute toxicity and metabolic changes caused by cadmium exposure on the fish Hyphessobrycon Callistus used as an indicator of environmental health: DOI: 10.15343/0104-7809.2012364574580 - Damato, Murilo (2012)
In Brazil, Hyphessobrycon callistus is an important commercially exploited species and it is an ideal animal for studyingdamages caused by the effects of heavy metal that are often detected in the aquatic environment. The main purpose of thepresent study was to detect the acute toxicity of Cd to H. callistus and investigate its effects on oxygen consumption, ammoniumexcretion, and the neutral red retention time assay to estimate effects at the cellular level. Such investigations havenot been carried out before with this species. Acute toxicity of Cd to H. callistus in 24h, 48h, 72h, and 96h medium lethalconcentration (LC50) was showed to be 45.95, 32.49, 28.28, and 15.16 mg/l, respectively. Furthermore, it was found thatexposure of fish to 1.5 mg/l Cd caused reduction in oxygen consumption and ammonium excretion of 59% and 71.5%,respectively as compared to controls.